Analisis Campuran Beraspal AC-BC Terhadap Penambahan Plastik LDPE (Low Density Polyethiline) - Dharmawan, Weka Indra; Oktarina, Devi; Septianto, Mendi (Rekayasa : Jurnal Ilmiah Fakultas Teknik Universitas Lampung, 2016)
Asphalt concrete is a road construction materials that have long been known and widely used in road construction. AC-BC is one of the three kinds of asphalt concrete mix that is AC-WC, AC-BC, and AC-Base. The use of AC-BC is one part of the pavement which serves as a layer between the maximum load bearing due to traffic loads. In general, a mixture of pavement materials AC-BC is composed of coarse aggregate, fine aggregate, filler and asphalt. This study aimed to know the ef- fect of the addition of Low Density Poly plastic types Ethilene (LDPE) on the quality of recycled asphalt mixture AC-BC, in terms of the Marshall parameters based on the specification of High - ways, 2010. The study was carried out experimentally in the laboratory with LDPE levels as much as 2%, 3%, 4%, 5% and 6% of the weight of the asphalt used to mix the two methods are the dry way and the wet way. The test results stated that the asphalt mixture with the addition of plastics with levels of 5% yield optimum performance if the terms of the strength, the stability of the value of 1360.06 kg (dry method) and 1398.77 kg (wet method), but overall the addition of plastic LDPE as a substitute ingredient mix asphalt on both the dry way and the wet way, giving the effect of an increase in the quality of hot mix asphalt.